Fonte de energia alternativa: um estudo sobre a percepção ambiental, social e econômica do biodiesel com docentes do Centro de Tecnologia do gás da cidade de Natal RN - Amorim, Marcel da Costa (2009)
Meaning fuel and renewal energy source s derivative additives, the term biodiesel exists in Brazil since 1980, when it was signed its first patent by Expedito Parente. Since then, its importance has grown gradually due to the worsening of the ambient problems, since its use has became a highly promising alternative to the pollution decrease, as in the carbon dioxide issue as with the smoke and sulfur oxide. In Brazil, it was created the National Program of Production, whose objective is to insert the new product in the country s energy matrix, strengthening the economy and creating new employment opportunities, being an important product to the national energetic independence, since Brazil still imports diesel to its domestic consumption. This study aims to identify the ambient, social and economic perception of the teachers from the Technology Center of Natal city (CTGÁS-RN) to the biodiesel. For that, it was used a questionnaire closed questions, organized in the likart scale, directed to the tree spheres of the research analysis, the biodiesel and its social, ambient and economic nuances, totaling 31 questionnaires full answered. In its objectives, the research was descriptive and in its approach it was qualitative. To the data analysis it was used statistical tools (Statistic software, 6.1 version and Microsoft Excel 2003). The research revealed the predominance of the ambient aspect in the sight of the teachers, followed by the social ones. The economic factors represent a minor percentage in the analysis when compared to other